Design and Development of Degradable Polyethylenimines for Delivery of DNA and Small Interfering RNA: An Updated Review. (24th December 2012) - Cho, Chong-Su
Abstract : Polyethylenimine (PEI), considered as the most potent and promising alternative carrier to viral vectors, has been studied as the "state of the art" among various polymers for nonviral gene delivery applications for many years. Although PEI-based carrier minimizes the bottlenecks associated with viral vectors such as unwanted immunogenicity and production problems, the toxic side effects of PEI prevent its rapid advancements due to nondegradable nature. In this regard, various degradable cross-linking and/or grafting agents have been linked to synthesize degradable PEIs in order to minimize the toxicity and improve the efficacy of PEI-mediated gene carriers. This paper describes an update on various cross-linkers and grafting agents in the design and development of degradable PEI derivatives and their potential applications for effective delivery of DNA in vitro and in vivo . The molecular weight (MW) of PEI and the structural relationship to its cellular toxicity and transfection ability were also discussed. Finally, the potential applications of various degradable PEIs for small interfering RNA (siRNA)-mediated gene silencing were also covered.